2022
DOI: 10.1126/sciadv.abk2746
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HER2-AXL heterodimerization to overcome resistance to HER2 blockade in breast cancer

Abstract: Anti-HER2 therapies have markedly improved prognosis of HER2-positive breast cancer. However, different mechanisms play a role in treatment resistance. Here, we identified AXL overexpression as an essential mechanism of trastuzumab resistance. AXL orchestrates epithelial-to-mesenchymal transition and heterodimerizes with HER2, leading to activation of PI3K/AKT and MAPK pathways in a ligand-independent manner. Genetic depletion and pharmacological inhibition of AXL restored trastuzumab response in vitro and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…2G ). This E-induced phosphorylation is of particular interest because it is consistent with previous studies that have suggested signaling crosstalk between AXL and HER2 to drive resistance to anti-HER2 therapy in breast cancer, as well as between AXL and EPHA2 or MET to confer resistance to EGFR inhibitors ( 17 , 28 , 50 , 51 ). Of similar interest is the fact that the RTK adapters Gab1/2, Eps8, Sos1, or Dapp1 as well as the E3-ubiquitin ligase Cbl-b are markedly downregulated in AXL KO, and that the phosphorylation of these proteins is dependent on the availability of AXL Y821, as evident from the fact that these phosphosites were not phosphorylated in the AXL Y821F cell line ( Fig.…”
Section: Resultssupporting
confidence: 86%
“…2G ). This E-induced phosphorylation is of particular interest because it is consistent with previous studies that have suggested signaling crosstalk between AXL and HER2 to drive resistance to anti-HER2 therapy in breast cancer, as well as between AXL and EPHA2 or MET to confer resistance to EGFR inhibitors ( 17 , 28 , 50 , 51 ). Of similar interest is the fact that the RTK adapters Gab1/2, Eps8, Sos1, or Dapp1 as well as the E3-ubiquitin ligase Cbl-b are markedly downregulated in AXL KO, and that the phosphorylation of these proteins is dependent on the availability of AXL Y821, as evident from the fact that these phosphosites were not phosphorylated in the AXL Y821F cell line ( Fig.…”
Section: Resultssupporting
confidence: 86%
“…For example, chemotherapy-induced AXL expression was reported in AML [ 65 ], lung cancer [ 66 ], prostate cancer [ 67 ], ovarian cancer [ 68 ], and endometrial cancer [ 69 ] as conferring therapy resistance. Recently, a series of studies linked AXL to several receptor tyrosine kinase inhibitors including EGFR inhibitors in lung cancer [ 70 ], head and neck cancer [ 71 ] and colorectal cancer [ 72 ], HER2 inhibitors in breast cancer [ 73 ], and FLT3 inhibitors in AML [ 74 ]. Identification of AXL as a leading feature in the sorafenib sensitivity prediction model further emphasizes its importance in resistance to receptor tyrosine kinase inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, Adam-Artigues and colleagues published on Science Advances a relevant work on the role of AXL in determining resistance to anti-HER2 therapy. 4 The authors first demonstrated that acquired trastuzumab-resistant HER2-positive breast cancer cells have significantly higher AXL expression than sensitive cells. In the resistant clones, AXL mediates the EMT and its genetic or therapeutic inhibition is sufficient to reduce migration and invasion capacity, EMT marker expression and acquired trastuzumab resistance.…”
Section: Targeting Her2-axl Heterodimerization To Overcome Resistance...mentioning
confidence: 99%